2017
DOI: 10.1021/acssuschemeng.7b03206
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Interface Engineering at TiO2/Dye through Molecularly Functionalized Caf1 Biopolymer

Abstract: The fast charge recombination kinetics and poor sensitizing ability in dye-sensitized solar cells (DSSCs) result in a significant electron loss and performance degradation. However, the retarding of electron recombination and/or increasing light-harvesting efficiency (LHE) via employing an appropriate interface modifier in DSSCs has rarely been investigated. Here, we firstly report a molecularly engineered Caf1 protein (both in monomeric and polymeric forms) to modify the surface states by effectively shieldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…It is also apparent that the pristine ZTO- and standard TiO 2 -based DSSC devices show a lower lifetime value, indicating low recombination resistance at the photoanode–electrolyte interface and decreasing carrier density. The J–V and EIS results obtained using ZTO, ZTO-ZnO, and ZTO-SnO 2 photoanode-based DSSC devices are compared with standard TiO 2 -based DSSC devices reported in the literature and summarized in Table . , Recently, Siwatch et al reported that the structured ZnO core provides a better electron transport pathway while the Zn 2 SnO 4 shell suppresses recombination by introducing an energy barrier between the core and oxidized dye or the electrolyte . Similarly, Li et al reported that the hierarchical SnO 2 /Zn 2 SnO 4 composite exhibits a maximum efficiency of 4.91% due to a large specific surface area and many active adsorption/interaction sites leading to higher light harvesting .…”
Section: Resultsmentioning
confidence: 99%
“…It is also apparent that the pristine ZTO- and standard TiO 2 -based DSSC devices show a lower lifetime value, indicating low recombination resistance at the photoanode–electrolyte interface and decreasing carrier density. The J–V and EIS results obtained using ZTO, ZTO-ZnO, and ZTO-SnO 2 photoanode-based DSSC devices are compared with standard TiO 2 -based DSSC devices reported in the literature and summarized in Table . , Recently, Siwatch et al reported that the structured ZnO core provides a better electron transport pathway while the Zn 2 SnO 4 shell suppresses recombination by introducing an energy barrier between the core and oxidized dye or the electrolyte . Similarly, Li et al reported that the hierarchical SnO 2 /Zn 2 SnO 4 composite exhibits a maximum efficiency of 4.91% due to a large specific surface area and many active adsorption/interaction sites leading to higher light harvesting .…”
Section: Resultsmentioning
confidence: 99%
“…The high‐frequency intercept on the real axis represents the series resistance (R s ) of the electrode which describes mainly the resistance of the two identical electrodes and the electrolytic resistance. [ 55,66 ]…”
Section: Resultsmentioning
confidence: 99%
“…The high-frequency intercept on the real axis represents the series resistance (R s ) of the electrode which describes mainly the resistance of the two identical electrodes and the electrolytic resistance. [55,66] We mainly emphasize on the R s and R ct of CEs. The R s and R ct parameters of these electrodes have been obtained by fitting the experimental data using a Randles-type equivalent circuit in Autolab impedance analyzer shown as an inset in Figure 9.…”
Section: Charge Transport Propertiesmentioning
confidence: 99%
“…[6][7][8][9] Among these PV technologies, DSSCs are a promising alternative to silicon solar cells in terms of low-cost raw materials, a facile fabrication process, and an extensive repertoire of materials. 10,11 Since the first report by O'Regan & Gratzel in 1991, the power conversion efficiency (PCE) of DSSCs has increased significantly above 15%. The DSSC industry has embraced a continuous effort in efficiency improvement and increasing attention in research through the engineering of materials, layers, and architectures.…”
Section: Introductionmentioning
confidence: 99%